The impact of Home Medication Review (HMR) in patients with type 2 Diabetes Mellitus (T2DM) living in rural areas in Kuantan, MALAYSIA - Zin, Che Suraya; Alias, Nor Elina; Ball, Patrick (2014)
OBJECTIVE: To investigate whether Home Medication Review (HMR) conducted by a pharmacist can improve the clinical indices, quality of life and medication adherence in patients with Type 2 Diabetes Mellitus (T2DM). METHOD: Six month prospective, randomized, controlled study. Adult T2DM patients taking medications for diabetes for at least two years, with HbA1c>8%, were recruited into the study and randomized to intervention or control. The intervention group received three home visits by a pharmacist (at baseline, 3 months and at 6 months), and one group counselling session with a dietician in addition to the standard medical care. Control group patients only received standard medical care. Primary outcome measures were HbA1c and fasting blood sugar (FBS). Secondary outcome measures include lipid profile (triglycerides, LDL- and HDL-cholesterol); blood pressure (BP); medication adherence (assessed using modified Morisky adherence scale); and quality of life (QoL) assessed using the Short form health survey (SF-36v2). Outcomes were evaluated at baseline, 3 months and at 6 months. RESULT: 73 patients were recruited to the intervention group (38) or the control group (35), with no significant difference identified in baseline parameters. Data was analysed in SPSSv19(IBM) using ANOVA and paired t-test. There were significant improvements from baseline to 6 months in the intervention group in; HbA1c (mean difference (MD) = 1.57, 95% CI[0.88, 2.26], p<0.001); FBS (MD=2.76, 95% CI[0.59,4.94], p=0.009); systolicBP (MD=6.56, 95% CI[0.75,12.36], p=0.022); diastolicBP (MD=4.44, 95% CI[1.11,7.78], p=0.006); triglycerides (MD=0.59, 95% CI[0.24,0.93], p<0.001) and medication adherence (MD=-2.19, 95% CI[-2.73,-1.65], p<0.001). The control group showed no significant changes in outcome measures. QoL improved in the intervention group but declined in controls. CONCLUSION: In this study, HMR conducted by a pharmacist provided significant improvement in health and QoL of patients with Type 2 Diabetes Mellitus. HMR may be beneficial for patients with chronic diseases and for the healthcare system.